2021
DOI: 10.4049/jimmunol.2001180
|View full text |Cite
|
Sign up to set email alerts
|

NK Cell Responses in Zika Virus Infection Are Biased towards Cytokine-Mediated Effector Functions

Abstract: Zika virus (ZIKV) is a mosquito-borne flavivirus that has emerged as a global concern because of its impact on human health. ZIKV infection during pregnancy can cause microcephaly and other severe brain defects in the developing fetus and there have been reports of the occurrence of Guillain-Barré syndrome in areas affected by ZIKV. NK cells are activated during acute viral infections and their activity contributes to a first line of defense because of their ability to rapidly recognize and kill virus-infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…On the other hand the reduction in IL-12 production, an essential cytokine for Th1 antiviral response, further indicates a nuanced dysregulation of APC antiviral signaling by mosquito saliva (36). The IL-12 reduction can downregulate the function of NK and CD8 + T cells, both extremely relevant to controlling ZIKV infection (40).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand the reduction in IL-12 production, an essential cytokine for Th1 antiviral response, further indicates a nuanced dysregulation of APC antiviral signaling by mosquito saliva (36). The IL-12 reduction can downregulate the function of NK and CD8 + T cells, both extremely relevant to controlling ZIKV infection (40).…”
Section: Discussionmentioning
confidence: 99%
“…A panel of 40 mAbs-transition metal conjugates was used to stain PBMCs ( S1 Table ). Cells were stained and prepared, as described elsewhere [ 16 ]. Cell events were acquired on the CyTOF-2 mass cytometer (Fluidigm) using CyTOF software version 6.7.1014 (Fluidigm) at the Plateforme de Cytométrie de la Pitié-Salpêtrière (CyPS) in Paris, France.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, our group previously reported in a sub-group of 16 Brazilian patients with acute ZIKV-infection, a massive activation of NK cells, some of which exhibited intracellular markers of immune activation, including a spontaneous ex vivo expression of phospho-STAT5. In addition, a proportion of these NK cells also spontaneously produced IFN-γ ex vivo in correlation with the STAT5 activation [ 16 ]. These results suggested the STAT5 pathway had been activated in vivo and might have lead to IFN-γ production into NK cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially recognized as part of a stereotyped innate immune mechanism, several reports have clearly shown that NK cells can acquire memory characteristics [ 6 , 7 , 8 , 9 ]. A role of memory-like NK cells (mlNKs) has been shown for cytomegalovirus [ 7 , 10 ], Zika virus [ 11 , 12 ], simian-human immunodeficiency virus (SHIV) [ 13 ], HIV [ 14 ], flu virus [ 15 , 16 ] as well as tuberculosis (TB) [ 17 , 18 ]. NK memory has also been reported against haptens [ 6 ] as well as a combination of IL12, IL15 and IL18 cytokines [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%